2019
DOI: 10.1103/physreve.100.032306
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the origin of urban-output scaling laws

Abstract: Urban outputs often scale superlinearly with city population. A difficulty in understanding the mechanism of this phenomenon is that different outputs differ considerably in their scaling behaviors. Here, we formulate a physics-based model for the origin of superlinear scaling in urban outputs by treating human interaction as a random process. Our model suggests that the increased likelihood of finding required collaborations in a larger population can explain this superlinear scaling, which our model predicts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…These discoveries provide an exciting context for developing a testable and predictive general science of cities. A number of theoretical models have been proposed as origins to superlinear scaling behaviours across cities [16,[19][20][21][22], but only some of these predictions actually give detailed predictions for exponent values. The proposed mechanisms relate social interactions driven by functional complementarities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These discoveries provide an exciting context for developing a testable and predictive general science of cities. A number of theoretical models have been proposed as origins to superlinear scaling behaviours across cities [16,[19][20][21][22], but only some of these predictions actually give detailed predictions for exponent values. The proposed mechanisms relate social interactions driven by functional complementarities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the underlying mechanisms of why inequality is systematically scaling with city size is of great future interest with many potential implications. Urban scaling theory in general proposes densifying interactions within cities as the fundamental process leading to the superlinear increase of many features [3,9,10,30,31]. Our analysis shows that the superlinear scaling is not seen within all subsections of the city.…”
Section: Discussionmentioning
confidence: 84%
“…These relationships can often be described by urban outputs, the scaling exponent β is greater than 1, suggesting greater rates of productivity (in both the positive and negative sense) in more populated cities. These observations, known as urban scaling, suggest that a small set of mechanisms significantly influence a variety of urban features across diverse cities [9,10]. Understanding these mechanisms has important implications for developing more prosperous and safer cities.…”
Section: Introductionmentioning
confidence: 99%
“…Bettencourt et al (2007) showed that serious crime in the United States exhibits superlinear scaling with exponent β ≈ 1.16 , and some evidence has confirmed similar superlinearity for homicides in Brazil, Colombia, and Mexico (Alves et al, 2013b;Gomez-Lievano et al, 2012). Previous works have also found that different kinds of crime in the United Kingdom and in the United States present nonlinear scaling relationships (Chang et al, 2019;Hanley et al, 2016;Yang et al, 2019). Remarkably, the existence of these scaling laws of crime suggests fundamental urban processes that relate to crime, independent of cities' particularities.…”
Section: More Crime In Cities?mentioning
confidence: 84%
“…Despite this inadequacy, we only have a limited understanding of the impact of nonlinearity on crime rates. Although previous works have investigated population-crime relationships extensively (Alves et al, 2013a;Bettencourt et al 2010;Chang et al 2019;Gomez-Lievano et al, 2012;Hanley et al, 2016;Yang et al, 2019), they have failed to quantify the impact of nonlinear relationships on rankings and restricted their analyses to either specific offenses or countries. The lack of comprehensive systematic studies has limited our knowledge on how the linear assumption influences crime analyses and, more critically, has prevented us from better understanding the effect of population on crime.…”
Section: Introductionmentioning
confidence: 99%